REFORM OF HIGHER EDUCATIONAL NURSES IN THE REPUBLIC OF UZBEKISTAN AND IMPROVING THE ROLE OF PRECEPTORS IN THE PRACTICE OF PATRONAGE NURSES IN CHILDREN'S INSTITUTIONS - Sattarova Zebo (Innovate Conferences, 2025)
Nursing is an important component of the healthcare system and is a field of activity aimed at solving the problems of personal and public health of the population in changing environmental conditions. The nurse should actively participate in informing and improving the health of the population, helping patients make the right choice in their relations with state, municipal and private healthcare systems. The nurse, within the scope of her competence, should participate in the development and implementation of collective measures aimed at improving the methods of combating diseases, warn patients, authorities and society as a whole about environmental hazards, and contribute to the organization of rescue services. The nursing association and the medical community as a whole should help attract nurses to areas of the country where medical care is underdeveloped, and should encourage them to work in such areas.
Keywords: Higher, educated, nurses, reform, primary health care institutions, patronage, nurses, practice, preceptors, role, improvement.